How the anterior, middle and posterior portions of the temporalis muscle work during mastication - Mirian Nagae; Fausto Bérzin; Marcelo Corrêa Alves; Maria da Graça Rodrigues Bérzin (Universidade Estadual de Campinas, 2015)
Aim: The aim of this study was to investigate mean electrical activity and how the anterior, middle, and posterior portions of the temporalis muscle work during mastication. Methods: The sample consisted of 16 healthy male college freshmen trichotomized, aged between 18 and 25 years, with Angle's Class I and no temporomandibular disorders. Electromyographic (EMG) recordings were made in anterior, middle and posterior portions of the temporalis muscle during mastication for 5 s. Results: It was found a significantly lower RMS value in the posterior portion (RMS: 1243.92) compared with those of the anterior (RMS: 2149.77) and middle (RMS: 2531.38) portions. Conclusions: There is an association between the portions of the temporalis muscle. It was found a significantly lower RMS value in the posterior portion showing that the anterior and middle portions of the muscle have a predominant function of maintaining movement during mastication.